1994
DOI: 10.1016/0013-4686(93)e0023-f
|View full text |Cite
|
Sign up to set email alerts
|

A contribution to the mechanism of “reduced” CO2 adsorbates electro-oxidation from combined spectroelectrochemical and voltammetric data

Abstract: The nature of reduced CO, adsorbates, as well as the mechanisms for their electro-oxidation on platinum, have been reviewed through the light of new experimental data obtained by cyclic voltammetry and by Fourier transform infrared reflectance spectroscopy. Three different "reduced" CO, adsorbates are described as "'ensembles". It is suggested that they involve different extents of adsorbed entities, among which weakly bound and strongly bound hydrogen atoms play the most important role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…Over Pt NPs, current densities for H 2 production are also lower than those under Ar atmosphere, although no CO 2 reduction product was detected. The self-poisoning of CO-like species on Pt decreases the coverage of surface adsorbed hydrogen [23], leading to lower current density for H 2 production over Pt NPs. Current densities for CO production over Pd NPs increase with pH, and becomes nearly the same as current densities for H 2 production under Ar atmosphere at pH higher than 2.2, suggesting that the majority of Pd active sites for HER under Ar atmosphere participate in CO 2 reduction under CO 2 atmosphere.…”
Section: Co 2 Reduction Activitymentioning
confidence: 98%
“…Over Pt NPs, current densities for H 2 production are also lower than those under Ar atmosphere, although no CO 2 reduction product was detected. The self-poisoning of CO-like species on Pt decreases the coverage of surface adsorbed hydrogen [23], leading to lower current density for H 2 production over Pt NPs. Current densities for CO production over Pd NPs increase with pH, and becomes nearly the same as current densities for H 2 production under Ar atmosphere at pH higher than 2.2, suggesting that the majority of Pd active sites for HER under Ar atmosphere participate in CO 2 reduction under CO 2 atmosphere.…”
Section: Co 2 Reduction Activitymentioning
confidence: 98%
“…The authors generally agree on the presence of linearly and bridge bonded CO species on Pt surface after CO 2 electrosorption [25,[27][28][29]36,38,48,[50][51][52][53][56][57][58][59], together with possible other adsorbates like COH [28,38,40,45], CHO [43] and COOH species [25,28,[30][31][32][33]41,47,50,59]. It was also postulated that CO 2 molecules only block hydrogen atoms, becoming blocked itself by water molecules and anions [26,44,46,51].…”
Section: Introductionmentioning
confidence: 97%
“…The process of CO 2 electrosorption on Pt and Rh depends on such factors as: potential and time of adsorption [28][29][30][31][32][33][34][35][38][39][40]45,46,[50][51][52][53][54][55]58,59], electrode surface morphology [41,51,55], method of electrode pretreatment [51,55] and solution composition [39,46,51,53,54] as well as plane orientation for single crystal electrodes [73][74][75][76][77][78]. The results of earlier experiments performed on noble metal alloys [6,[79][80][81][82][83][84] have showed that in general the surface coverage, structure and composition of the adsorption product are dependent on the alloy surface composition.…”
Section: Introductionmentioning
confidence: 99%
“…Efficient catalysts for CO2 reduction should provide both the activation of CO2 and the subsequent hydrogenation to reduced species. For this reason, metals with low hydrogen overpotentials, such as Pt and Pd, have been widely used since these materials adsorb easily hydrogen [4][5][6][7]. Adsorbed hydrogen favours the adsorption of species derived from CO2 on the electrode surface, since the formation of "reduced CO2" adsorbates requires interaction between CO2 molecules and adsorbed hydrogen [4,5,7].…”
Section: Introductionmentioning
confidence: 99%